Macromol. Chem. Phys. 8/2015. Issue 8 (April 2015) - Ge, Xueping; Ye, Qiang; Song, Linyong; Misra, Anil; Spencer, Paulette
<x xml:space="preserve">Abstract</x> Front Cover: Polymers cured by free‐radical/cationic ring‐opening hybrid polymerization under visible‐light irradiation are studied to determine the effects of photo‐polymerization kinetics and chemical miscibility on their crosslinking structure and mechanical properties. The chain transfer reaction between the epoxy group of the epoxide and the hydroxyl group of the methacrylate plays an important role in the formation of the crosslinking network, not only enhancing the crosslinking density, but also preventing the micro‐sized phase separation. Further details can be found in the article by X. Ge, Q. Ye, * L. Song, A. Misra, and P. Spencer* on page 856. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>